Models and methods in social network analysis - Carrington, Peter J., 1946-; Scott, John, 1949-; Wasserman, Stanley (Structural analysis in the social sciences ;, 2005)
"Models and Methods in Social Network Analysis presents the most important developments in quantitative models and methods for analyzing social network data that have appeared during the 1990s. Intended as a complement to Wasserman and Faust's Social Network Analysis: Methods and Applications, it is a collection of original articles by leading methodologists reviewing recent advances in their particular areas of network methods.